Optimization of solid phase extraction for simultaneous quantification of efavirenz and levonorgestrel in wastewater using HPLC - Munzhelele, E. P.; Ayinde, W. B.; Gitari, W. M.; Mudzielwana, R. (Frontiers in Environmental Science, 2025)
This study aims to optimize the SPE parameters for purification and preconcentration of EFV and LVG to enable optimum detection and quantification by LC-20 Prominence High-Performance Liquid Chromatography (HPLC) system. The gradient elution method was used to profile and quantify efavirenz (EFA) and levonorgestrel (LVG). The optimized parameters were solution pH, solvent type and concentration, and elution volume. The 60 mg/3 mL Hydrophilic-lipophilic balance (HLB) was used to extract the target pharmaceutical contaminants. The percentage recoveries of EFA and LVG ranged from 67% to 83% and 70% to 94.61%, respectively at an optimal pH of 2, solvent concentration and type 100% Methanol and an elution volume of 4 mL using HLB cartridges. The method’s accuracy was validated by obtaining a correlation coefficient (R2) > 0.98 from the respective calibration curves of the target contaminants. The limit of detection (LOD) and limit of quantification (LOQ) for efavirenz were 0.705 µg/L and 0.14 µg/L, respectively, and for levonorgestrel, they were 0.061 µg/L and 0.199 µg/L. The optimized SPE method was used to extract wastewater samples, and the yield results showed that the method could be applied for the simultaneous detection of efavirenz and levonorgestrel, demonstrating its potential applications in environmental research. The concentration of EFA ranged from 0.36 to 8.10 µg/L in influent samples and 2.88 to 8.11 µg/L in effluent samples. Conversely, the concentration of levonorgestrel ranged from 2.64 to 32.31 µg/L in influent samples and 2.32 to 12.35 µg/L in effluent samples. The obtained results were validated by analyzing these samples using ultra-high-performance liquid chromatography. Based on the results, the optimized Solid Phase Extraction (SPE) method can be used to pre-concentrate EFA and LVG in wastewater samples, inspiring future research.